Análise comparativa do desempenho de um motor de indução trifásico tradicional e um motor de indução trifásico assimétrico com alimentação monofásica - Prado, Wellington do (2013)
The main objective of this work is to perform a comparative study between a three phase induction motor squirrel cage traditional and asymmetrical three-phase induction motor. Were used two motors of the same power, the motor being powered by an asymmetrical voltage source phase. In the studies we investigated the behavior of various quantities such as yield, starting current, voltage sags, power factor, and the power supplied by each machine. With the results obtained from practical experiments, it was found that the asymmetric motor features a number of advantages over traditional engines, which makes it an excellent choice when the application requires the drive loads of high power and not has a three-phase supply.